Friend or enemy? Review of 17β‐HSD10 and its role in human health or disease. Issue 3 (23rd May 2020) - Vinklarova, Lucie; Schmidt, Monika; Benek, Ondrej; Kuca, Kamil; Gunn‐Moore, Frank; Musilek, Kamil
Abstract: 17β‐hydroxysteroid dehydrogenase (17β‐HSD10) is a multifunctional human enzyme with important roles both as a structural component and also as a catalyst of many metabolic pathways. This mitochondrial enzyme has important functions in the metabolism, development and aging of the neural system, where it is involved in the homeostasis of neurosteroids, especially in regard to estradiol, changes in which make it an essential part of neurodegenerative pathology. These roles therefore, indicate that 17β‐HSD10 may be a possible druggable target for neurodegenerative diseases including Alzheimer's disease (AD), and in hormone‐dependent cancer. The objective of this review was to provide a summary about physiological functions and pathological roles of 17β‐HSD10 and the modulators of its activity. Abstract : 17β‐hydroxysteroid dehydrogenase (17β‐HSD10) is a multifunctional human enzyme with important roles both as a structural component but also as a catalyst of many metabolic pathways. This mitochondrial enzyme has important functions in the metabolism, development and aging of the neural system, where it is involved in the homeostasis of neurosteroids, especially in regard to estradiol, changes in which make it an essential part of neurodegenerative pathology. In this review, 17β‐HSD10 role as a possible druggable target for neurodegenerative diseases including Alzheimer's disease is indicated, but it also has become apparent that it may have a role in hormone dependent cancer.